2011
DOI: 10.1016/j.intimp.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the carotenoid astaxanthin on phagocytic capacity and ROS/RNS production of human neutrophils treated with free fatty acids and high glucose

Abstract: In summary, this study showed that both high glucose and a mixture of FFA are potent inducers of ROS/RNS production on neutrophils as observed by higher levels of superoxide anion, hydrogen peroxide and NO production. Also, these metabolites decrease the phagocytic capacity of neutrophils and increase the G6PDH activity. Overall, ASTA-treatment was able to reduce partially ROS/RNS production by reducing the availability of NADPH and recover phagocytic capacity of neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…On the other hand, another group evaluated the effect of palmitic acid on human neutrophil reactive oxygen species production using luminol-enhanced chemiluminescent (Wanten et al, 2002) and found that this fatty acid, at 1 mM, induces the production of significant amounts of radical oxygen species in the absence of any neutrophil stimulus. Additionally, a study performed in isolated human neutrophils reported a stimulatory effect of a mixture of fatty acids (the most abundant components of this mixture were palmitic (31%) and stearic acids (41%)) on the production of reactive oxygen species (Guerra and Otton, 2011). These findings suggest a role of palmitic acid (depending on its concentration) on reactive oxygen species production by neutrophils, which may be relevant for the inflammatory process and tissue damage and for the host organism's protection against pathogenic microorganisms.…”
Section: Long-chain Saturated Fatty Acids (Lcsfas)mentioning
confidence: 99%
“…On the other hand, another group evaluated the effect of palmitic acid on human neutrophil reactive oxygen species production using luminol-enhanced chemiluminescent (Wanten et al, 2002) and found that this fatty acid, at 1 mM, induces the production of significant amounts of radical oxygen species in the absence of any neutrophil stimulus. Additionally, a study performed in isolated human neutrophils reported a stimulatory effect of a mixture of fatty acids (the most abundant components of this mixture were palmitic (31%) and stearic acids (41%)) on the production of reactive oxygen species (Guerra and Otton, 2011). These findings suggest a role of palmitic acid (depending on its concentration) on reactive oxygen species production by neutrophils, which may be relevant for the inflammatory process and tissue damage and for the host organism's protection against pathogenic microorganisms.…”
Section: Long-chain Saturated Fatty Acids (Lcsfas)mentioning
confidence: 99%
“…The maximum activity of this enzyme was previously described by Guerra and Otton [35] and was based on the conversion of NADP + in NADPH in the presence of glucose-6-phosphate.…”
Section: Lymphocyte Antioxidant and Metabolic Enzyme Activitymentioning
confidence: 99%
“…), sun proofing (O'Connor & O'Brien ; Suganuma et al . ), antidiabetic activities (Maoka & Etoh ; Guerra & Otton ) and among other various health benefits due to the potent antioxidant activity of this fat‐soluble pigment. Astaxanthin exists in various stereoisomers characterized by different configuration of the two hydroxyl groups on the molecule (Fig.…”
Section: Introductionmentioning
confidence: 99%